Letter to Jane Tolmach; from E.F. Galioni - E.F. Galioni:::::: (1966)
This letter is to inform Jane Tolmach about the meeting of trustees and superintendents on February 3rd and 4th are cancelled. The reason why both meetings got canceled was due to the Department of Mental Hygiene needed to time to budget review since it is an important for consideration in the state of California. The meeting was rescheduled to be held on February 15 at 9:30 am.